من شعرية اللساني إلى غواية الرقمي : قراءة في النص الرقمي " عياش" لـــــ عبد الرحمن الأخضري - لباشي, عبد القادر (جامعة الوادي - university of Eloued, 2021)
تبحث هذه الدراسة في الانتقال الذي حصل بسرعة، من ثقافة الكلمة إلى ثقافة الصورة في عصر شهد تطورات الحياة الاجتماعية والثقافية، وهيمنة الوسائط التكنولوجية، وتحولات جوهرية فيكل الفنون، فصرنا مثلا أمام شاعر رقمي، يسعى إلى الاغتراف من مصادر شتى، لتشكيل قصيدة مؤثرة، اكتسابالمتلق جديد مختلف عن المتلقي التقليدي.و لبيان ذلكسيكون الرهان على النص الرقمي" عياش" للشاعر عبد الرحمن الأخضري الذي استعان بهذه الوسائط لتقديم نوع جديد من النصوص. انطلاقا من هذا الفهم، يتبدّى إشكال هذا الموضوع فيما يأتي: ما مفهوم الأدب الرقمي؟ وما حدود اشتغاله؟وما مدى تناسق عناصر هذه التجربة في هذا النص، وهو يوظّف الأداء الصوتي واللوني والتركيب، والحركة، لينتج بلاغته الرقمية؟ الكلمات المفتاحية: اللّسان، التفاعلية، الصورة، الرقمية Abstract This study examines the transition that took place quickly, from the culture of the word to the culture of the image in an era that witnessed the developments of social and cultural life, the dominance of technological media, and fundamental transformations in all the arts, so we became an example in front of a digital poet seeking to scoop up from various sources, to form an influential poem, Acquisition of a new recipient that is different from a traditional recipient. To demonstrate this, betting will be on the digital text "Ayyash" by the poet Abdul Rahman Al-Akhdari, who used these media to present a new type of text. Based on this understanding, the problem of this topic becomes clear in the following: What is the concept of digital literature? What are the limits of his operation? How consistent are the elements of this experience in this text, as he employs sound, color, composition, and movement performance to produce his digital rhetoric? key words: langue, interactive, image, digital
مقال
Keywords: اللّسان، التفاعلية، الصورة، الرقمية